The Prospects for the Development of Extreme Tourism in Uzbekistan - Mikhliev Mukhammadali; Mallayeva Sarvinoz (Web of Journals Publishing, 2023)
The tourism industry in Uzbekistan has long been focused on traditional forms of tourism, such as visiting historical monuments and cultural sites. However, in recent years, there has been a growing interest in extreme tourism, which offers travelers the opportunity to explore Uzbekistan's stunning natural beauty and unique cultural heritage through activities such as mountain climbing, trekking, and paragliding. This article examines the prospects for the development of extreme tourism in Uzbekistan, including the current state of the industry, the potential benefits and challenges, and the steps that can be taken to support its growth. The article also considers the impact of extreme tourism on local communities and the environment, and the importance of sustainable practices in promoting its long-term success.
Keywords: Tourism industry, extreme tourism, natural and cultural heritage sites, Uzbekistan, younger travelers, mountain climbing, trekking, and paragliding.